1972
DOI: 10.1104/pp.49.6.919
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Translocation in Sugar Beet Petioles in Relation to Petiolar Respiration and Adenosine 5′-Triphosphate

Abstract: Earlier studies have shown that the retarding effect of low petiolar temperatures on sucrose transport through sugar beet (Beta vulgaris L.) petioles is markedly time-dependent. Although the initial effect of chilling the petiole to near 0 C is severely inhibitory, translocation rates soon recover (usually within about 2 hours) to values at or near the control rate. In the present studies, selected metabolic parameters were measured simultaneously with translocation. No stoichiometric relationships among petio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1972
1972
1981
1981

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…The carbohydrate accumulation in the leaf, which may be caused by petiole cooling, can be calculated from measured rates of net photosynthesis and the initial inhibitions of translocation which other workers have obtained with the same system and species (1,19). The value obtained for carbohydrate accumulation of 0.15 mg cm-2 leaf area is of the same order of magnitude as the increase in carbohydrate levels which resulted from infection in the environment of experiment I.…”
Section: Discussionmentioning
confidence: 53%
“…The carbohydrate accumulation in the leaf, which may be caused by petiole cooling, can be calculated from measured rates of net photosynthesis and the initial inhibitions of translocation which other workers have obtained with the same system and species (1,19). The value obtained for carbohydrate accumulation of 0.15 mg cm-2 leaf area is of the same order of magnitude as the increase in carbohydrate levels which resulted from infection in the environment of experiment I.…”
Section: Discussionmentioning
confidence: 53%
“…The steady-state labeling system was similar to that described by Coulson et al (3). Both the level of radioactivity in the gas stream and the level of CO2 could be monitored.…”
mentioning
confidence: 80%
“…The translocation system is generally divided into three structurally and physiologically distinct regions: the source, path, and sink regions. Recent structural and physiological studies (5,10,17,18) have indicated that the path region is relatively passive in the translocation process, in that the driving force for transport resides in metabolism-dependent processes operating in the source and sink regions.From a mechanistic viewpoint, the major emphasis in the phloem transport literature has been toward elucidating the role of the path at the expense of source and sink metabolism, particularly at the cellular level. Recent studies by Geiger and co-workers (12, 13) have investigated events operating in the source leaf of Beta vulgaris during the loading of sucrose into the phloem prior to translocation.…”
mentioning
confidence: 99%
“…The translocation system is generally divided into three structurally and physiologically distinct regions: the source, path, and sink regions. Recent structural and physiological studies (5,10,17,18) have indicated that the path region is relatively passive in the translocation process, in that the driving force for transport resides in metabolism-dependent processes operating in the source and sink regions.…”
mentioning
confidence: 99%